Pembuatan Biodiesel Dari Cpo Off Grade Menggunakan Reaktor Membran - Firman Maulana; Syarfi Syarfi; Ida Zahrina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The cost of biodiesel production process is still a challenge, it needs to explore any raw material which is economically inexpensive and effective technologies to overcome the problem. CPO off grade is deemed economically potential to be processed into biodiesel because its inexpensive cost . Membrane reactor is an alternative technology that need to be developed to address this challenge . The research aimed to study the effect of oil to methanol mole ratio and transmembrane pressure on biodiesel production from CPO Off Grade . The study was conducted using two- step process , namely the process of esterification and transesterification process . Esterification process was carried out with variation of oil to methanol mole ratio of 1:12. The amount acid catalyst used is 2 % by weight of oil and reaction time of 2 hours . Transesterification process is carried out on membrane reactor with variation of oil to methanol mole ratio of 1:12 , 1:16 and 1:20 and transmembrane pressure of 1 bar , 1.5 bar , 2 bars and a catalyst concentration of 1 wt% base oil and process temperature of 60 º C. The results showed the highest conversion reached 80.14 % at the mole ratio of 1:20 and transmembrane pressure of 2 bar Keywords : Biodiesel, CPO Off Grade, Membrane Reactor, Mole ratio, Transmembran Pressure.